A Comparative Study of Rapid SARS-Cov-2 Antigen Detection Assay against RT-PCR Assay for Diagnosis of COVID-19 in a Tertiary Hospital of Kathmandu - Chaudhary, R.; Bhatta, S.; Singh, A.; Pradhan, M.; Moktan, B.; Duwal, S.; Pandit, R. (Kathmandu University Medical Journal, 2022)
Background The Coronavirus disease 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus (SARS-CoV-2) has spread worldwide since its first recorded case in the city of Wuhan, China, in December 2019. SARS-CoV-2 infection causes asymptomatic to sever pneumonia. Severe cases may develop acute respiratory disease syndrome (ARDS), with an average mortality rate of 6.9%. Real Time Reverse Transcriptase Polymerase Chain Reaction (rRT-PCR) assay is the current reference standard laboratory method for the diagnosis of SARS-CoV-2 infection. However, it takes around 6-8 hours to get the result and is time consuming. Therefore, rapid and accurate tests for SARS-CoV-2 screening are essential to expedite disease prevention and control. Lateral flow immunoassay using monoclonal anti SARS-CoV-2 antibodies which target for SARS-CoV-2 antigen can be complimentary screening test if their accuracy were comparable to that of the real time reverse transcription-polymerase chain reaction (RT-PCR) assay. Objective To find the sensitivity and specificity of a rapid antigen test kit in comparison to reverse transcription-polymerase chain reaction (RT-PCR). Method A cross-sectional hospital based study was carried out at Shree Birendra Army Hospital, Kathmandu for a period of four months. Result Our finding shows sensitivity and specificity of rapid diagnostic tests (RDT) Ag kit as 60.6% and 96.4% respectively. Positive and negative predictive value was 83.7% and 89.0%. Likewise, positive and negative likelihood ratio was 17.0 and 0.4. The overall accuracy of the antigen kit was 88.1% in comparison to reverse transcription-polymerase chain reaction (RT-PCR) as the gold standard. Conclusion Our study concluded the use of rapid antigen kit is mainly useful for screening purposes.